Modernisasi dan Digitalisasi Public Servis: Mewujudkan Indonesia Emas Melalui Harmonisasi Sistem Pemerintahan Berbasis Elektronik (SPBE) - Hadi, Ilham; Widnyani, Ida Ayu Putu Sri (Jurnal Kridatama Sains dan Teknologi, 2024)
To achieve "Golden Indonesia" in 2045, Indonesia must make many changes and adjustments that are relevant to international progress. Modernization in the fields of science, technology, and information communication is essential because this progress will have a major impact on many aspects of human life and various parts of government, including public services. The government is implementing SPBE (Electronic-Based Government System), previously known as e-Government, as a result of advances in information and communication technology. The purpose of SPBE itself is to build an integrative, dynamic, transparent, and innovative government, as well as to improve the quality of integrated, efficient, responsive, and adaptive public services. Therefore, the purpose of this study is to explain and analyze the role and effectiveness of the Electronic-Based Government System (SPBE) in government modernization or the digitalization of public services. This is done to show the strategic steps taken by the government and ensure that SPBE is a crucial part of the development of modernization and digitalization in achieving Golden Indonesia 2045. This study uses a descriptive-analytical study, and a literature review is used (Library Research). This is done to provide a comprehensive overview and analysis of the modernization and digitalization of public services through the implementation of the Electronic-Based Government System (SPBE) and align it with the strategic objectives of Indonesia Emas 2045. To ensure the usefulness and validity of the data, the researcher uses source triangulation techniques to compare information from various literatures. The results and findings in this study indicate that the implementation of SPBE is an absolute prerequisite and also functions as a supporting factor in realizing the vision and mission of "Indonesia Emas 2045." In addition, this study also views that simultaneously the Human Development Index also plays a dominant role in the success of the implementation of SPBE both in the scope of government agencies and bureaucracy and in the community as the main element.